Cellular imaging by targeted assembly of hot-spot SERS and photoacoustic nanoprobes using split-fluorescent protein scaffolds - Tuğba Köker (Nature Portfolio, 2018)
Traditional methods for the assembly of plasmonic nanoparticles into photo-responsive probes suffer from multiple problems. Here the authors use split fluorescent protein fragments as molecular glue to form stable nanoclusters for surface enhanced Raman scattering and photoacoustic imaging in live cells.